Synergistic Cytotoxic and Antimigratory Effect of Brazilein and Doxorubicin on HER2-Overexpressing Cells - Handayani, Sri (Asian Pacific Organization for Cancer Prevention, 2022)
Objective: The present research aims to report cytotoxic and antimigratory activities of the oxidized form of brazilin, i.e., brazilein, and the effects of the combination of brazilein-doxorubicin on MCF-7/HER2 cells. Methods: The MTT assay was conducted to test the cytotoxic activity, while flow cytometry with PI and PI-annexin V staining were respectively performed for cell cycle and apoptosis analyses. Migration and invasion analyses were assessed via Boyden chamber assay, while HER2, Rac1, p120, MMP2, and MMP9 protein levels were determined by immunoblotting and gelatin zymography. Molecular docking of ligands with HER2, Src, PI3Kα, PI3KΔ, and PI3Kγ proteins was evaluated using MOE 2010. Results: The MTT assay showed that the IC50 value of brazilein against MCF-7/HER2 cells was 51 ± 2.1 μM. Moreover, brazilein and its combination with doxorubicin-induced G2/M accumulation and apoptosis. Combination of brazilein-doxorubicin inhibited cell migration and tended to decrease HER2, Rac1, p120, MMP2, and MMP9 protein expression levels. Based on our molecular docking study, the docking score of brazilein with PI3Kγ is comparable to that of the native ligand. Conclusion: Taken together, a combination of brazilein-doxorubicin exhibited synergistic cytotoxic and antimigratory effects on MCF-7/HER2 cells. © This work is licensed under a Creative Commons Attribution-Non Commercial 4.0 International License.